INVESTIGATION OF THE QUALITATIVE AND QUANTITATIVE COMPOSITION OF WOOLEN FABRICS IN PHYSICO-CHEMICAL METHODS (Scientific journal of the Fergana State University, 2024)
The analysis of the structure of textiles has been carried out, studies of their chemical composition have been carried out and appropriate conclusions have been drawn. A number of methods have been used to ensure the reliability of methods for determining the chemical composition of fabrics consisting of a mixture of wool and silk fibers. The use of methods varied from simple to complex. The first organoleptic, the second microscopic, the third chemical and the fourth IR-spectrometric Fourier methods were used. The organoleptic method shows the specific characteristics of fiber combustion. Gorenje Microscopically, microscopic images of wool and silk fibers were made compared to images of other fibers. Chemically, the qualitative and quantitative composition of wool and silk fibers was carried out by a chemical method, that is, by dissolving the wool fiber in an appropriate solvent, as well as by examining residues. In the spectrometric method, their chemical composition was determined by the physico-chemical method by comparing the calculated IR spectra with the spectra contained in the base of the IR Fourier spectra. All stages of the study of the qualitative and quantitative composition of two-component products, i.e. wool and silk fibers, are widely disclosed in the article, and logically concluded with the relevant conclusions.